QuantiFERON-TB® Gold Plus as a potential tuberculosis treatment monitoring tool. Issue 3 (23rd March 2017) - Kamada, Arisu; Amishima, Masaru
Novel approaches to controlling tuberculosis (TB) are required, especially in light of the growing number of multidrug-resistant pathogens [1]. The results of sputum smears and culture are often insensitive or slow to detect treatment failure and acquired drug resistance. The lack of biomarker assays for treatment monitoring is listed among the main requirements for next generation assays, as identified among the global TB community [2]. The surrogate CD8 response of QuantiFERON-TB Plus is a potential monitoring aid during treatment for active TB http://ow.ly/2eNb308prn6